Protection of the surface weathering stone artworks by a chemical conversion method. (10th September 2018) - Liu, Yan; Yang, Fuwei; Zuo, Guofang; Zhang, Ruixiang; Wei, Guofeng; Ma, Qiang
Abstract: A chemical conversion method for the protection of the surface weathering stone artworks was explored. By this method, the harmful calcium sulfate weathering layer on the stone relics was converted into a protective calcium oxalate layer in situ . The calcium oxalate conversion layer was characterized by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, X-ray diffraction (XRD) and polarizing microscope (PLM). The conversion layer was also estimated by chromatic aberration, capillary suction, adhesive force and dissolution stability tests. The calcium oxalate conversion layer with good weatherability, adherence and compatibility will be promising as a solution for the protection of the surface weathering rock relics.